Effect of size on single and double optical microbottle resonator humidity sensors - Johari, Md Ashadi Md; Abdul Khudus, Muhammad Imran Mustafa; Jali, Mohd Hafiz; Al Noman, Abdullah; Harun, Sulaiman Wadi (Elsevier, 2018)
An experimental study on the effect of whispering gallery mode (WGMs) on micro-bottle resonator (MBR) and its application on humidity sensing is presented. Different transmission mode spectra observed when the diameter of MBR (Db) change from 130μm to 190μm. The Q-factor for single and double MBRs ware observed >104 for all cases. The size and number of MBRs effecting Q-factor value which are high Q-factor value for smallest size Db=130μm for single MBR and Pair-4 (combination of two biggest MBRs Db=190μm) for double MBRs. Application of single and double MBRs in humidity sensing received various sensing performance. With the highest sensitivity value, linearity >90% and P-value >10-13 make MBR with diameter 130μm to be the best performance as humidity sensor for all cases. Both single and double MBRs are stable over 60 seconds. Overall, the size of the MBR has been shown to be more important than the quantity of MBRs for humidity sensing. Indeed, double MBRs actually perform worse than single MBRs as humidity sensors.